PENINGKATAN PENGETAHUAN HIV /AIDS PADA KARYAWAN PERKANTORAN SEBAGAI UPAYA PENANGANAN HIV/AIDS PADA USIA PRODUKTIF - Yudha, Raden Rama Widya Kartika; Isnugroho, Hernawan; Sulistyowati, Endang Tri (Jurnal Pengabdian Masyarakat Karya Husada (JPMKH), 2023)
Abstract: HIV/AIDS has become an epidemic throughout the world, including in Indonesia, including office workers. The increase in cases of transmission every year and the absence of proper education are of particular concern. Efforts to prevent the spread of HIV/AIDS can be done by increasing the understanding of people of productive age. Efforts to prevent transmission and eliminate stigma based on education for office employees can be carried out as an effort to increase public awareness of HIV and prevention of transmission, as well as its handling. Education is carried out by presentation and question and answer methods using the media "power point slides" accompanied by posters and "stickers" which contain information about preventing HIV transmission in office employees at PT. Batania Alti, as well as screening of a short film containing education to stop the stigma against HIV/AIDS sufferers followed by providing support in the form of free haircuts to the participants after the educational activities took place. By using language that is communicative and close to the target, showing short films and distributing posters and stickers increases the target's knowledge in preventing HIV/AIDS transmission. This is marked by the target's ability to answer the questions given and retell the contents of the educational material.